Can fruit and vegetable aggregation systems better balance improved producer livelihoods with more equitable distribution?. (December 2021) - Cooper, G.S.; Shankar, B.; Rich, K.M.; Ratna, N.N.; Alam, M.J.; Singh, N.; Kadiyala, S.
Highlights: Aggregation boosts farmer revenues but risks diverting fruit and vegetable supply away from consumers in small rural markets. Via a systems model set in Bihar, India, we identify levers to make horticultural aggregation more relevant to small markets. Market-based cold storage and boosting small market demand offer policy levers to improve spatial equity in consumption. Intervention combinations improve small market fruit and vegetable availability, whilst avoiding farmer revenue trade-offs. Packages of synergistic policies should be embraced to foster 'win-wins' in nutrition-sensitive food systems. Abstract: The need for food systems to generate sustainable and equitable benefits for all is a global imperative. However, whilst ample evidence exists linking smallholder farmer coordination and aggregation (i.e. the collective transport and marketing of produce on behalf of multiple farmers) to improved market participation and farmer incomes, the extent to which interventions that aim to improve farmer market engagement may co-develop equitable consumer benefits remains uncertain. This challenge is pertinent to the horticultural systems of South Asia, where the increasing purchasing power of urban consumers, lengthening urban catchments, underdeveloped rural infrastructures and inadequate local demands combine to undermine the delivery of fresh fruits and vegetables to smaller, often rural or semi-rural markets serving nutritionally insecure populations. To this end, we investigate the potential for aggregation to be developed to increase fruit and vegetable delivery to these neglected smaller markets, whilst simultaneously improving farmer returns. Using an innovative system dynamics modelling approach based on an aggregation scheme in Bihar, India, we identify potential trade-offs between outcomes relating to farmers and consumers in smaller local markets. We find that changes to aggregation alone (i.e. scaling-up participation; subsidising small market transportation; mandating quotas for smaller markets) are unable to achieve significant improvements in smaller market delivery without risking reduced farmer participation in aggregation. Contrastingly, combining aggregation with the introduction of market-based cold storage and measures that boost demand improves fruit and vegetable availability significantly in smaller markets, whilst avoiding farmer-facing trade-offs. Critically, our study emphasises the benefits that may be attained from combining multiple nutrition-sensitive market interventions, and stresses the need for policies that narrow the fruit and vegetable cold storage deficits that exist away from more lucrative markets in developing countries. The future pathways and policy options discovered work towards making win–win futures for farmers and disadvantaged consumers a reality.